Genome Sequencing Variations in the Octodon degus, an Unconventional Natural Model of Aging and Alzheimer's Disease - Hurley, Michael J.; Urra, Claudio; Garduno, B. Maximiliano; Bruno, Agostino; Kimbell, Allison; Wilkinson, Brent; Marino-Buslje, Cristina; Ezquer, Marcelo; Ezquer, Fernando; Aburto, Pedro F.; Poulin, Elie; Vasquez, Rodrigo A.; et al. (Frontiers in Aging Neuroscience, 2022)
The degu (Octodon degus) is a diurnal long-lived rodent that can spontaneously develop molecular and behavioral changes that mirror those seen in human aging. With age some degu, but not all individuals, develop cognitive decline and brain pathology like that observed in Alzheimer's disease including neuroinflammation, hyperphosphorylated tau and amyloid plaques, together with other co-morbidities associated with aging such as macular degeneration, cataracts, alterations in circadian rhythm, diabetes and atherosclerosis. Here we report the whole-genome sequencing and analysis of the degu genome, which revealed unique features and molecular adaptations consistent with aging and Alzheimer's disease. We identified single nucleotide polymorphisms in genes associated with Alzheimer's disease including a novel apolipoprotein E (Apoe) gene variant that correlated with an increase in amyloid plaques in brain and modified the in silico predicted degu APOE protein structure and functionality. The reported genome of an unconventional long-lived animal model of aging and Alzheimer's disease offers the opportunity for understanding molecular pathways involved in aging and should help advance biomedical research into treatments for Alzheimer's disease.